Evaluation of Sch 29482 in experimental syphilis and comparison with penicillin G benzathine in disseminated disease and localized infection. - Baughn, R E (1984)
The present study was designed to assess the in vivo activity of Sch 29482, a new penem antibiotic, against disseminated and localized Treponema pallidum infections in rabbits. Animals were inoculated either intravenously or intradermally. Randomized groups then received 25 or 50 mg of Sch 29482 per kilogram of body weight twice a day for 7 days, two weekly injections of 200,000 U of penicillin G benzathine for comparative purposes, or no antibiotic therapy. In both infection models, striking differences were noted between the untreated control rabbits and rabbits receiving penicillin G benzathine or high-dose Sch 29482. Intravenously infected rabbits did not develop disseminated lesions or orchitis, and chancres produced by intradermal infection regressed and healed rapidly after both treatment regimens. Infectivity studies also suggested that high-dose Sch 29482 and penicillin G benzathine were effective since the testes and lymph nodes of treated animals were free of infectious organisms. Treatment of animals with the lower dose of Sch 29482 represented borderline or suboptimal therapy, with a failure rate of one in four for each infection model.